2011
DOI: 10.4161/cc.10.6.15080
|View full text |Cite
|
Sign up to set email alerts
|

Identification of dAven, aDrosophila melanogasterortholog of the cell cycle regulator Aven

Abstract: Irusta (2011) Identification of dAven, a Drosophilamelanogaster ortholog of the cell cycle regulator Aven, Cell Cycle, 10:6, 989-998,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 81 publications
0
11
0
Order By: Relevance
“…1 of Ref. [34]). The exception to this is the Drosophila ortholog of Aven (dAven) that was recently identified by Zou and coworkers [34].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…1 of Ref. [34]). The exception to this is the Drosophila ortholog of Aven (dAven) that was recently identified by Zou and coworkers [34].…”
Section: Resultsmentioning
confidence: 99%
“…[34]). The exception to this is the Drosophila ortholog of Aven (dAven) that was recently identified by Zou and coworkers [34]. Interestingly, the Drosophila protein does not contain a recognizable BH3 motif: the conserved L and D residues as well as other amino acids are not preserved (e.g., an F at position 4a that AVEN shares with BIM and BAD and which makes a significant hydrophobic contribution to the BH3 domain interactions of these proteins; Supplemental File 1) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While most studies have focused on the abdominal fat body and its role as the analog of the mammalian liver, recent studies have suggested the fat body surrounding the brain functions in housing factors that help to establish the sexual identity of the brain (24). In mammals, it is known that the hypothalamic-pituitary-adrenal axis (HPA), which responds to stress, is influenced by sex hormones such as testosterone and estrogen (55). In one study, researchers found that feminization of the androgen receptor can cause higher HPA Seconds Spent Highly Mobile Fig.…”
Section: Discussionmentioning
confidence: 99%